2020
DOI: 10.17221/247/2019-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid bacteria on Listeria monocytogenes infection and innate immunity in rabbits

Abstract: The present study aimed to investigate the effect of probiotic lactic acid bacteria (LAB) addition on Listeria monocytogenes translocation and its toxin listeriolysin O (LLO), proinflammatory factors, immune organ indexes and serum immunoglobulins in farmed rabbits. Five treatments included negative control (NC), positive control (PC) with L. monocytogenes infection and supplemental LAB at 3.0 × 10<sup>6 </sup>(low-LAB, L-LAB), 3.0 × 10<sup>8</sup> (medium-LAB, M-LAB) and 3.0 × 10<su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…In the present study, the mortalities between treatments were not statistically different (data not shown), and the growth performance was not measured due to the short duration of feeding trial, but the symptoms of birds in the control treatment were consistent with the known knowledge that animals suffered from listeriosis showed some clinical signs such as restlessness, loss of appetite, fever, and nervous system disorders ( Papić et al., 2019 , Zhao et al., 2020 ). Notably, dietary Lactobacilli significantly inhibited L. monocytogenes proliferation in the gastrointestinal tract and its invasion into other critical organs in broilers.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, the mortalities between treatments were not statistically different (data not shown), and the growth performance was not measured due to the short duration of feeding trial, but the symptoms of birds in the control treatment were consistent with the known knowledge that animals suffered from listeriosis showed some clinical signs such as restlessness, loss of appetite, fever, and nervous system disorders ( Papić et al., 2019 , Zhao et al., 2020 ). Notably, dietary Lactobacilli significantly inhibited L. monocytogenes proliferation in the gastrointestinal tract and its invasion into other critical organs in broilers.…”
Section: Resultssupporting
confidence: 83%
“…Serum levels of proinflammatory cytokines IL-1β, IL-2, IL-6, IFN-γ, and anti-inflammatory IL-4, IL-10 changed linearly or quadratically both at the initial and final phases of broilers fed with E. faecium NCIMB 11181 ( Wu et al., 2019 ). Mucosa listeriolysin O mRNA expression and serum TNFα, IL1β, and IFNγ were reduced by a cocktail of L. acidophilus , L. plantarum , and E. faecium , but indexes of thymus and spleen, serum IgA, and IgG were increased in farm rabbits ( Zhao et al., 2020 ). Anyway, the interrelation among virulence property of pathogens, inflammatory response of hosts, and the probiotics deserves more studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, animals can carry L. monocytogenes without appearing sick, and shed the bacteria in their feces (Papić et al, 2019). Rabbit meat with low fat and high proteins is becoming popular (Dalle Zotte and Szendrő, 2011;Ding et al, 2019a;Wang et al, 2019b,c); however, investigations show that farm rabbits are susceptible to L. monocytogenes and their meat is also a source of listerial foodborne pathogen (Rodríguez-Calleja et al, 2006;De Cesare et al, 2017;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus acidophilus reduces Listeria monocytogenes infection by inhibiting mitogen-activated protein... Zhao et al that dietary lactic acid bacteria attenuated listerial infection and virulence but improved innate immunity in rabbits (Zhao et al, 2020) and broilers (Deng et al, 2020). Host mitogen-activated protein kinase (MAPK) links multiple signaling pathways in response to a myriad of stimuli including bacterial infections.…”
Section: Introductionmentioning
confidence: 99%